KONDISI FISIK PEMAIN SEKOLAH SEPAKBOLA (SSB) DIKPORA WELERI - Nanda Dimas Dwi Putra; Husnul Hadi; Pradipta Dwi Galih, (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2025)
This research aims to determine the physical condition of the Dikpora Weleri City Football School players. The type of research used is descriptive. The population of this study consisted of 100 people aged 14 15 years. The research sample was 22 people. Data collection was carried out by carrying out physical condition tests, namely: arm muscle strength with the push-up test, abdominal muscle strength with the sit-up test, leg muscle explosive power with the standing broad jump test, agility with the arrowhead agility test, speed with the running test 30 meters, endurance with a 1,200meter running test. Data obtained through research test instruments were analyzed using a percentage formula. The results of this study show that: 1) Arm muscle strength with an average of 39.0% is in the moderate category, 2) Abdominal muscle strength with an average of 42.00% is in the poor category, 3) Leg muscle explosive power with an average of 35.0% is in the medium category, 4) Agility with an average of 59.0% is in the medium category, 5) Speed with an average of 42.0% is in the medium category, 6) Endurance with an average of 53.0% is in the medium category. The conclusion from all the tests in this study is that the physical condition of the weleri City football school players is in the medium category. The players are expected to have more motivation to train physically in accordance with need.